UNIVERSAL MATRIX MODEL OF FORMATION OF COMPETENCE WITH ACCOUNT OF THE FUNCTIONS OF ACTIVITY AND MEASUREMENT OF LEARNING RESULTS BASED ON DUBLIN DESCRIPTORS - Riabchykov , M.; Khurana , Karan (Problems of Engineer-Pedagogical Education, 2019)
A conclusion on the need of the reciprocal movement of employers and educators in the process of formulating specialist competencies was drawn on the base of the analysis of the priorities of the European Commission. The justification for the principles of the formulation of competencies based on the functions of the activities that are determined by the employer is proposed. The basic oxonmetric proposals for the formulation of the functions of the activity have been developed and substantiated. The design, material, technological, instrumental managerial, business functions were identified. Proposed functions are compared with the curriculum for training specialists in several areas. The principles of measuring of learning outcomes based on Dublin descriptors are defined. It was proposed to strengthen the share of the “autonomy and responsibility” descriptor, the justifications for its formation and measurements are given. For this descriptor in the formation of all the components of competence, formulated with the functions of the activity, it is recommended to provide a real practical result. The forms of training, the most rational for the formation of learning outcomes in accordance with the descriptors of "knowledge", "skills", "communication", "autonomy and responsibility" are substantiated. A matrix model for the formation of competencies based on learning outcomes has been developed. A qualimetric approach to the measurement of learning outcomes is substantiated, on the basis of which the result of training is formed in an explicit form. A criterion for the formation of competences in the form of the surface of learning outcomes is proposed. The real level of competence of a specialist is compared with the requirements of the employer. The possibility of a non-stationary level of learning outcomes was revealed.Comparison of a given and real competence of a specialist should be made by groups of experts in the conditions of the counter policy of employers and educational institutions. The proposed approaches are implemented in the preparation of curricula for a number of specialties.